Fiction and Social Theory: E-Special Introduction. (December 2016) - Beer, David
This E-Special issue brings together a range of articles from the Theory, Culture, & Society archive that directly explore the relations between fiction and social theory. Each article develops a different perspective on these relations, yet they all share a common interest in probing at the different ways in which fiction might enrich and provoke our conceptual imaginations. These articles ask how theory might be used to understand or illuminate fiction, whilst also considering how theory might be extended, challenged or informed by fictional resources. In general terms, the articles take three types of overlapping approach. First, there are those that use fiction to extend the imagination of social theory. Second are the articles that use fiction as a documentary resource and platform for theorizing. And, finally, there are those articles that use theory to reanimate and re-examine fictional forms. In exploring these three intersecting branches the pieces illustrate the different ways in which fiction and social theory might interweave in our thinking. The articles gathered here provide frameworks, ideas and resources through which the reader might continue to think imaginatively and creatively about the social world.